Cold vengeance [large type] - Mehl, Nancy (Mehl, Nancy. Ryland & St. Clair (Series), 2024)
"When a renowned crime podcaster vanishes without a trace, former FBI behavioral analysts turned private investigators River Ryland and Tony St. Clair are called upon to track her down. As they wade through the evidence she left behind, they unearth a startling connection -- she may have discovered the existence of an unknown killer, and he will stop at nothing to carry out a deadly plan. As the pair delves deeper, they soon find themselves the targets of a relentless enemy determined to silence them. With their lives -- and hearts -- on the line, can they confront the evil that threatens them before it consumes them both?"--